Cloned aerolysin of Aeromonas hydrophila is exported by a wild-type marine Vibrio strain but remains periplasmic in pleiotropic export mutants. - Wong, K R (1990)
With a wide host range vector, the structural gene aerA for the hole-forming extracellular protein aerolysin of Aeromonas hydrophila was cloned into the marine Vibrio sp. strain 60 and into three pleiotropic export mutants (epr mutants). The parent strain and all of the mutants were able to express the protein with the aerA promoter in the plasmid. The parent strain exported proaerolysin into the medium, while all of the mutants accumulated the protoxin in their periplasms. Two of the mutants also accumulated protease; however, as we have found earlier with A. hydrophila, the periplasmic form of proaerolysin in the Vibrio sp. must somehow be protected from proteolysis because it was not converted to active toxin until the cells were shocked. Conversion could be prevented by adding o-phenanthroline to the solutions used in shocking. These results show that the export pathway in the marine Vibrio sp. is very similar to the pathway in A. hydrophila.